Prognostic value of hemoglobin, albumin, lymphocyte, platelet (HALP) scores in patients with non-valvular atrial fibrillation: insights from the AFTER-2 study - Serdar Söner; Tuncay Güzel; Adem Aktan; Raif Kılıç; Hülya Tosun Söner; Muhammed Demir; Ahmet Ferhat Kaya; Ercan Taştan; Metin Okşul; Adnan Duha Cömert; Gamze Yeter Arslan; Erkan Baysal; et al. (BMC Cardiovascular Disorders)
Abstract Objectives The relationship between hemoglobin, albumin, lymphocyte, platelet (HALP) score, and various cancers and cardiovascular diseases has been tested previously. However, the relationship between HALP score and non-valvular atrial fibrillation (NVAF) has not been adequately tested. Therefore, our study aimed to investigate the relationship between HALP score and mortality in patients with NVAF. Methods This study included 2,592 NVAF patients from 35 centers in Turkey. Patients were divided into two groups: those with HALP scores ≤ 58.96 (low HALP score group, 1,296 patients) and > 58.96 (high HALP score group, 1,296 patients). The primary outcome measured was all-cause mortality. Results The mean HALP score was 66 ± 33. Patients in the low HALP score group had higher 1- and 5-year all-cause mortality rates (1-year: 12.9% vs. 5.4%, p < 0.001; 5-year: 38.5% vs. 20.2%, p < 0.001). Cox regression analysis identified the HALP score as an independent predictor of mortality (1-year: HR = 0.987, 95% CI = 0.981–0.992, p < 0.001; 5-year: HR = 0.990, 95% CI = 0.987–0.993, p < 0.001). ROC analysis determined a HALP score 52.3 predicted 1-year mortality with 62.9% sensitivity and 62% specificity (AUC = 0.680); a score of 55 predicted 5-year mortality with 60.3% sensitivity and 62.2% specificity (AUC = 0.657). Kaplan-Meier analysis revealed increasing mortality over time in the low HALP score group (log-rank tests, 1-year = 44.86, p < 0.001; 5-year = 108.54, p < 0.001). Conclusions The HALP score is a simple, accessible measure, and our findings suggest that lower HALP scores are associated with increased 1-year and 5-year mortality in NVAF patients. This provides a reference for clinicians assessing risk in this vulnerable population. Graphical Abstract